ECONOMIC AND SOCIAL IMPACT OF ASSESSING SUSTAINABLE STRATEGIES IN UZBEKISTAN - Usmonov Oybek Ulugbekovich (European Science Publishing, 2025)
This article explores the economic and social impact of assessing sustainable strategies in Uzbekistan, a country rich in natural resources yet facing significant challenges related to environmental sustainability and economic development. Through a critical analysis of current sustainability initiatives, the article highlights the implications of these strategies on the economic landscape and social fabric of Uzbek society. It identifies key areas where sustainable practices can yield positive outcomes, such as improved livelihoods, enhanced quality of life, and increased resilience against climate change. Furthermore, it discusses the role of governmental and non-governmental organizations in fostering a sustainable future for Uzbekistan by emphasizing community engagement and participatory approaches.
Keywords: Sustainable strategies, Uzbekistan, economic impact, social impact, environmental sustainability, community engagement.